A STUDY ON EVULATING AWARENESS OF AI TOOLS AMONG THE FACULTY MEMBER (International Journal of Food and Nutritional Sciences, 2022)
AI technology continues to advance rapidly, it offers numerous innovative tools and applications that can revolutionize the teaching and learning process. However, the successful integration of these AI tools into academic settings relies on faculty members' awareness and understanding of their capabilities. The purpose of this study is to evaluate the awareness of AI tools among the faculty members. The technique used in this study is one sample t-test. The outcome of the study indicated that Research rabbit, Scispace, ChatGPT, Elicit, Grammarly, ChatPDF, Gamma, Scite, Quill Bot, and paper pal have high awareness surrounding them. Whereas, Trinka (grammar checker), Grade scope, Consensus and Jenni AI have low awareness. Further studies can be conducted analysing impact of Artificial Intelligence in education sector.